Protection Motivation and the COVID-19 Virus. Issue 1 (2nd January 2021) - Kowalski, Robin M.; Black, Kelly J.
ABSTRACT: The current study examined the role of the components of the Protection Motivation Theory of Health (PMT) in predicting protective health behaviors related to the COVID-19 virus. Through a snowball sampling procedure, in Wave 1 424 respondents completed a survey in March 2020. One hundred thirteen of these participants completed the same survey in Wave 2 in May 2020. Consistent with research on SARS, females and older individuals engaged in the behaviors more often than men and younger individuals. After accounting for these variables in predicting frequency of protective health behaviors, components of the PMT accounted for an additional 12% of the variance in Wave 1 and 16% in Wave 2, with perceived severity and outcome efficaciousness correlating positively with frequency. Anticipatory regret mediated the relationship between PMT and protective health behavior frequency. The results suggest that public health announcements that are tailored toward the severity of the virus and the efficacy of the health behaviors in decreasing the spread of the virus may meet with more success than those that heighten people's vulnerability to the disease.